Diversity Management Strategies in Multicultural Organizations: Challenges and Opportunities - Silalahi, Verry Albert Jekson Mardame; Rumambi, Freddy Johanis (Indonesian Journal of Advanced Research, 2024)
This research explores diversity management strategies in multicultural organizations, addressing challenges and opportunities arising from cultural, ethnic, gender, and demographic differences. With globalization, workplaces are becoming increasingly diverse, offering benefits but also challenges. This study employs a descriptive qualitative approach through a literature review to analyze diversity management strategies in global organizations. The findings highlight major challenges such as intercultural conflict, implicit bias, and cross-cultural communication barriers. Effective strategies include diversity training, anti-discrimination policies, and fostering an inclusive work environment. Properly managed diversity enhances creativity, innovation, and decision-making while broadening an organization’s global market reach. Practically, organizations are advised to develop inclusiveness policies and provide diversity training to promote workplace harmony. Theoretically, this study enriches diversity management literature by presenting a new approach to addressing workplace diversity. Future research should focus on empirical studies to deepen understanding of strategy implementation across various organizational contexts.